Role of Judiciary in Protecting Witnesses in the Criminal Justice System: A Critical Analysis - Parwez , Zahid; Sarangi, Narayan Chandra; Jabbal , Dolly (International Journal of Membrane Science and Technology, 2023)
Witnesses are the eyes and ears of the Criminal Justice System. Witnesses being the only spectator of an offence are the indispensable aid in the Criminal Justice Delivery System but are yet at a vulnerable position that they turn victims at several instances. Starting from the investigation stage to the trial proceedings of the court witness assist the Court in every possible way to punish the accused person by deposing every relevant fact which can lead to a fair justice delivery and conviction of the accused person without getting any gain. Witnesses are often subjected to threatening, inducement, harassment, and different kinds of intimidation to them and also their family members. Due to this, in many cases due to lack of Witness Protection Laws the witnesses not getting adequate protection they become victims. Unlike the accused, the witnesses or victims have no rights for their protection. And when the state agencies fail to do their duty, as has often happened in many cases in the recent past, the witnesses turn out to be a victim and subsequently left to suffer injustice silently. Protection of witness is also one of the attributes of fair trial which is guaranteed under Article 21 of the Constitution of India wherein proper safety and security should be ensured. But due to lack of effective Witness Protection Regime and statutory framework for giving protection in our country the witness has lost confidence when it’s about their safety and security. This has also given rise to high acquittal rate and decrease in convictions in the justice administration system. The Judiciary has actively given importance for having witness protections Laws in India and at the same time has enumerated the duties of Witnesses towards the state when the state is providing protection.